Pemahaman Recount Text oleh Siswa Kelas 10 SMA Harapan 1 - Jamal, Wan Karmenita; Siregar, Lisna Sari (Universitas Harapan Medan, 2025)
This research investigates the comprehension of recount texts among 10th grade students class B at SMA Harapan 1 Medan. This research explores the factors influencing the quality of students' understanding and assesses their English performance in this context. This research aims to identify common challenges students face and to propose effective teaching strategies to improve their comprehension of recount texts. This research used the theory of Brown, (2001). Utilizing a case study method, data was collected from 26 from 27 students in 10th grade class b 2023/2024 academic year. This This research using the case-method were the writer come to school and observe using pre-test, post-test and interview methods. The pre-test and post-test measure students' progress in understanding recount texts, while interviews provide deeper insights into their experiences and challenges. The findings highlight issues in factors and the level of students' understanding on recount text. This research offers insights into improving instructional practices and ultimately enhancing students' language proficiency and academic performance. Recommendations include continued use of structured instruction, development of varied learning materials, enhanced teacher support, interactive learning environments, and further research into effective teaching strategies and technology use to improve literacy skills and academic performance.